AI-READI: rethinking AI data collection, preparation and sharing in diabetes research and beyond - Baxter, Sally L.; de Sa, Virginia R.; Ferryman, Kadija; Jain, Prachee; Lee, Cecilia S.; Li-Pook-Than, Jennifer; Liu, T. Y. Alvin; Owen, Julia P.; Patel, Bhavesh; Yu, Qilu; Zangwill, Linda M.; Bahmani, Amir; et al. (Nature metabolism, 2024)
Here, we introduce Artificial Intelligence Ready and Equitable Atlas for Diabetes Insights (AI-READI), a multidisciplinary data-generation project designed to create and share a multimodal dataset optimized for artificial intelligence research in type 2 diabetes mellitus.